Suboptimal Baseline Serum Vitamin B12 Is Associated With Cognitive Decline in People With Alzheimer’s Disease Undergoing Cholinesterase Inhibitor Treatment - Cho, Hsiao Shan; Huang, Li Kai; Lee, Yao Tung; Chan, Lung; Hong, Chien Tai (Frontiers in Neurology, 2018)
Objectives: Cholinesterase inhibitors (ChEIs) are the mainstream treatment for delaying cognitive decline in Alzheimer’s disease (AD). Low vitamin B12 is associated with cognitive dysfunction, and its supplementation has been applied as the treatment for certain types of reversible dementia. The present study hypothesized that baseline serum vitamin B12 is associated with the deterioration of cognitive function in people with AD undergoing ChEI treatment. Materials and Methods: Between 2009 and 2016, medical records from 165 Taiwanese with mild to moderate AD underwent ChEI treatment for at least 2 years were reviewed. Their baseline serum vitamin B12 levels were measured before treatment initiation. Their cognitive function was assessed using the Mini-Mental State Examination (MMSE) and Cognitive Abilities Screening Instrument (CASI). Student’s t test and multivariable logistic regression were used to analyze the association between cognitive decline and vitamin B12 level. Statistical analyses were performed using SPSS 19.0. Results: Overall, 122 participants were women. Their median age was 76-year-old (ranging from 54 to 91). For people with optimal baseline vitamin B12 (above the median level of 436 ng/L), the rates of MMSE and CASI decline were 0.78 ± 1.28 and 2.84 ± 4.21 per year, respectively, which were significantly slower than those with suboptimal vitamin B12 (1.42 ± 1.67 and 4.94 ± 5.88 per year; p = 0.007 and 0.009, respectively). After adjustment for age, sex, education level, hypertension, diabetes, history of stroke, and baseline cognitive function, the baseline serum vitamin B12 level was negatively associated with MMSE and CASI decline. Conclusions: Suboptimal baseline serum vitamin B12 level is associated with cognitive decline in people with AD undergoing ChEI treatment.